2023
DOI: 10.1039/d2qo01972h
|View full text |Cite
|
Sign up to set email alerts
|

Iron porphyrin-catalysed C(sp3)–H amination with alkyl azides for the synthesis of complex nitrogen-containing compounds

Abstract: With the readily prepared iron porphyrin complex as a catalyst and starting with alkyl azides, a panel of nitrogen-containing skeletons representing the families of natural alkaloids and bioactive compounds could be prepared in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Other examples are related to the processes of the CÀ N bond formation catalyzed by iron or ruthenium containing compounds, e. g. [48,49] Theoretical studies on methane hydroxylation reaction with presence of aromatic cyclic compounds containing Ru or Fe were performed by Sharma et al [50] Another example is experimental and theoretical study of the reactivity patterns and reaction mechanisms in e. g. alkane hydroxylation catalyzed by a mononuclear nonheme ruthenium(IV)-oxo com-plex, [Ru IV (O)(terpy)(bpm)] 2 + . [51] It was showed that in the alkane hydroxylation process, the experimental and theoretical results revealed that the dissociation of the substrate radical formed via a rate-determining hydrogen atom abstraction of an alkane C À H bond is more favorable energetically than other processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other examples are related to the processes of the CÀ N bond formation catalyzed by iron or ruthenium containing compounds, e. g. [48,49] Theoretical studies on methane hydroxylation reaction with presence of aromatic cyclic compounds containing Ru or Fe were performed by Sharma et al [50] Another example is experimental and theoretical study of the reactivity patterns and reaction mechanisms in e. g. alkane hydroxylation catalyzed by a mononuclear nonheme ruthenium(IV)-oxo com-plex, [Ru IV (O)(terpy)(bpm)] 2 + . [51] It was showed that in the alkane hydroxylation process, the experimental and theoretical results revealed that the dissociation of the substrate radical formed via a rate-determining hydrogen atom abstraction of an alkane C À H bond is more favorable energetically than other processes.…”
Section: Introductionmentioning
confidence: 99%
“…Other examples are related to the processes of the C−N bond formation catalyzed by iron or ruthenium containing compounds, e. g [48,49] . Theoretical studies on methane hydroxylation reaction with presence of aromatic cyclic compounds containing Ru or Fe were performed by Sharma et al [50] .…”
Section: Introductionmentioning
confidence: 99%